2012
DOI: 10.1097/ccm.0b013e3182657b5d
|View full text |Cite
|
Sign up to set email alerts
|

Trial of shift scheduling with standardized sign-out to improve continuity of care in intensive care units*

Abstract: A shift-work schedule with structured sign-out curriculum is a viable alternative to traditional work schedules for the intensive care unit in training programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…29,30,[33][34][35][36]41,43,46 A minority of studies found a favorable impact on resident well-being (4 of 17, 24%; TABLE 2). 32,33,45,48 When analyzed by intervention type, the most frequent result of shift length changes was no impact (8 of 20, 40%), 23,24,27,28,31,32,34,35 that of night float was an unfavorable impact (10 of 18, 56%), [35][36][37][38][39][41][42][43]46,47 and for protected time for sleep, 1 study reported a favorable outcome for resident wellness (1 of 2, 50%) 48 but no impact on patient care, while the other study was unfavorable for resident well-being (1 of 2, 50%). 49 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…29,30,[33][34][35][36]41,43,46 A minority of studies found a favorable impact on resident well-being (4 of 17, 24%; TABLE 2). 32,33,45,48 When analyzed by intervention type, the most frequent result of shift length changes was no impact (8 of 20, 40%), 23,24,27,28,31,32,34,35 that of night float was an unfavorable impact (10 of 18, 56%), [35][36][37][38][39][41][42][43]46,47 and for protected time for sleep, 1 study reported a favorable outcome for resident wellness (1 of 2, 50%) 48 but no impact on patient care, while the other study was unfavorable for resident well-being (1 of 2, 50%). 49 …”
Section: Resultsmentioning
confidence: 99%
“…There were 27 studies included in the final review: 13 (48%) reviewed shift length, [23][24][25][26][27][28][29][30][31][32][33][34][35] 12 (44%) examined Across all of the studies and interventions, the impact of duty hour restrictions most frequently had no impact on patient care (5 of 10, 50%), 23,24,28,41,48 no impact on resident well-being (7 of 17, 41%), 27,34,35,41,44,46,49 and an unfavorable impact on resident education (9 of 14, 64%). 29,30,[33][34][35][36]41,43,46 A minority of studies found a favorable impact on resident well-being (4 of 17, 24%; TABLE 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations